If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + 6x = -6x + 113 Reorder the terms: 5 + 6x = 113 + -6x Solving 5 + 6x = 113 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 5 + 6x + 6x = 113 + -6x + 6x Combine like terms: 6x + 6x = 12x 5 + 12x = 113 + -6x + 6x Combine like terms: -6x + 6x = 0 5 + 12x = 113 + 0 5 + 12x = 113 Add '-5' to each side of the equation. 5 + -5 + 12x = 113 + -5 Combine like terms: 5 + -5 = 0 0 + 12x = 113 + -5 12x = 113 + -5 Combine like terms: 113 + -5 = 108 12x = 108 Divide each side by '12'. x = 9 Simplifying x = 9
| 0=-10v^2+13v+3 | | 3x-7=-1+6x | | 2(8+4k)=3k-4 | | -2x+1=-5x+31 | | 4(8-6x)=5x-26 | | 5x^2+75x+270=0 | | x+8=-16+4x | | 32+6x=8(x+3) | | 2(5x-25)=10(x-5) | | 6+3x=-3x-6 | | -7x^2-64+112=0 | | -9+5x=3x+9 | | 2(7v+7)=28+7v | | 7-7x=2x+7 | | 11x^2-37x=0 | | 2(1-2n)=2n+8 | | -9+2x=4x-17 | | 18x^2+3x-10=0 | | -4x^2-4x+168=0 | | 3-x=8(1-6x)-5 | | 7m^2-35m=0 | | 6x^2+42x+60=0 | | 9m^2-54m=0 | | 6x+9=199-5x | | 8+4r=8(-7r+1) | | 6(1+2k)=-k+19 | | X-2(x-3)=-6-5x | | 2-m(5+mx)=3m^2(1-mx) | | 7(-4m+2)=34-8m | | 4x-9=3+4x | | a*b*c=154 | | abc=154 |